Determinan Perilaku Merokok Remaja SMA/Sederajat di Kecamatan Lowokwaru Kota Malang - Muslim, Nadzifa Azhar; Adi, Sapto; Ratih, Suci Puspita; Ulfah, Nurnaningsih Herya (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2023)
Background. Smoking behavior among adolescents tent to increase every year. Adolescent smoking behavior was influenced by various factors from the individual factors or environmental factors. Aim. The purpose of this study is to identify the determinants of smoking behavior in Lowokwaru district, Malang city. Method. The research method is a quantitative with a cross-sectional study design. The research was heald in January 2023. Data was collected through the Tobacco Retailer Assessment and Questionnaire (TRAQ) website. The research population were 17.120 from all senior high school students. There were 330 students randomly selected from 3 schools in different sub-districts. Data was analyzed with chi-square test and multiple logistic regression. Result. The results showed that knowledge and attitude (p-value = 0,000), access to cigarette (p-value = 0,000), and parental exposure cigarettes at home (p-value = 0,022) were associated with adolescent smoking behavior. The multivariate results showed that access to the availability of cigarettes is the most influential factor on smoking behavior. Conslusion. Adolescent smoking behavior in Lowokwaru District is influenced by knowledge and attitudes, access to cigarette, and parental exposure cigarettes at home. Recommendation to raise the cigarettes price so that are not easily accessible to children and adolescents.